55.4k views
3 votes
What is 4(4m-3)-(m-5)=52 step by step

User Etse
by
5.5k points

1 Answer

5 votes

Answer:

-3

Explanation:

Simplifying

4(4m + -3) + -1(m + -5) = -52

Reorder the terms:

4(-3 + 4m) + -1(m + -5) = -52

(-3 * 4 + 4m * 4) + -1(m + -5) = -52

(-12 + 16m) + -1(m + -5) = -52

Reorder the terms:

-12 + 16m + -1(-5 + m) = -52

-12 + 16m + (-5 * -1 + m * -1) = -52

-12 + 16m + (5 + -1m) = -52

Reorder the terms:

-12 + 5 + 16m + -1m = -52

Combine like terms: -12 + 5 = -7

-7 + 16m + -1m = -52

Combine like terms: 16m + -1m = 15m

-7 + 15m = -52

Solving

-7 + 15m = -52

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '7' to each side of the equation.

-7 + 7 + 15m = -52 + 7

Combine like terms: -7 + 7 = 0

0 + 15m = -52 + 7

15m = -52 + 7

Combine like terms: -52 + 7 = -45

15m = -45

Divide each side by '15'.

m = -3

Simplifying

m = -3

Hope this helped :)

User Sprocket
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.